Evaluasi Gameplay pada Game Arknights menggunakan Metode Analisis Mechanics, Dynamics and Aesthetics (MDA) Framework - Yuan Edo Ramadhana; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
There are quite a lot of video games published in various genres in this age, with one of the genres being strategy games. Strategy games rely on the player's ability to think critically while formulating a strategy in order to reach the game's goal. Strategy games are divided into several sub-genres, including tower defense. One of the tower defense video game available to download at the moment is Arknights. Currently Arknights has a positive reception from various users, scoring 4.6 stars at Google Play. However, a lot of players also had difficulties while playing, citing level difficulty and lack of resources received as main issues. Based on aforementioned issues, author conducts an analytic research using MDA Framework method, which refers to the analysis over the mechanic, dynamic and aesthetic aspects of a video game. This method is done by doing a solo testing and a playtesting session with several respondents, then conducting interviews with aforementioned respondents. Based on the analysis results from conducted interviews, recommendations that can be propsed to Arknights includes raising the possibility to obtain resources, accelerating automatically refilled resource refills, reducing resource consumption on several levels, and balancing the properties owned by enemy agents.